The impact of online customer service and store features on consumer experience and willingness to revisit their preferred online store - Miriam Tiutiu; Sefora Nemțeanu; Dan-Cristian Dabija; Corina Pelau (Humanities & Social Sciences Communications)
Abstract From aspects scarcely studied, such as the online store ambiance and display of the product in the online store, to more prevalent issues related to purchasing behaviour, such as online customer service, the ethics of online stores, and online technologies, this article develops and tests a conceptual model of the factors that significantly impact consumer interactions, experience, behaviour and their willingness to revisit online stores. Data collected from 272 Romanian online shoppers during 2021–2022 is analysed by structural equation modelling with SmartPLS. The results highlight a positive link between online customer service, consumer behaviour, and store ambiance. Ethics of online sales positively influence consumer behaviour within the online store. Online store technology is significantly associated with consumer behaviour and online store interaction. The paper extends the theory of Planned Behaviour, highlighting significant links between online consumer service and other factors and their implications on online purchasing behaviour and on the willingness to return to the online store.